Continuation of the Ross–Delamerian Orogen: insights from eastern Australian detrital-zircon data. Issue 7 (17th November 2018) - Shaanan, U.; Rosenbaum, G.; Sihombing, F. M. H.
Abstract: Information on the Paleozoic tectonic evolution of the Tasmanides in eastern Australia is limited due to the presence of an extensive younger sedimentary cover. Based on the spatio-temporal distribution of deformation and magmatism, the Tasmanides have traditionally been subdivided into five domains (Delamerian, Thomson, Lachlan, Mossman and New England). To test the relationships between these domains, we compiled over 10000 published detrital-zircon ages from basement rocks of the Tasmanides. We split the dataset spatially to test postulated connectivity between domains, and temporally to isolate corresponding age populations that can highlight subtle variations between domains. Results show that the Delamerian and Thomson domains originated as a single orogenic belt that likely received detritus from an early Paleozoic continental-scale drainage system. We also recognise a remarkably similar pattern of Paleoproterozoic and Archean ages in the Delamerian, Thomson and New England domains. This similarity indicates that the late Paleozoic development of the New England domain involved recycling of rocks from the Delamerian–Thomson domain(s). These findings shed new light on the crustal architecture of eastern Australia, and the nature of Paleozoic drainage and sediment recycling in eastern Gondwana.